The Impact of Organizational Factors Causing Work Stress on Job Alienation: An Applied Study at Mutah University (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
This study aims to analyze the impact of the organizational factors that cause work stress on job alienation at Mutah University. To achieve  the objectives of the study, a questionnaire was developed and distributed to a sample that involved (400) participants; (370) questionnaires were retrieved, while (360) were useful for analysis. The statistical Package for the Social Science (SPSS.19) was used in processing and analyzing data in an attempt to answer the study questions and to test its hypothesis. The study has concluded that the level of the organizational factors causing work stress at mutah university came at a medium level, with an arithmetic mean of (3,00). The level of Job Alienation came at a medium level, and with an arithmetic mean (2,68). The study also found that there was an effect for that organizational factors causing work stress and all its dimensions on job alienation and all its dimensions. The study recommended the need to conduct further research to analyze the impact of personal factors causing work stress on job alienation or organizational commitment.
Keywords: Functionality; Servant Leadership